Impact of electrostatic potential on microcapsule-formation and physicochemical analysis of surface structure: Implications for therapeutic cell-microencapsulation. (October 2021) - Santos, Ana Paula; Chevallier, Sylvie Swyngedau; de Haan, Bart; de Vos, Paul; Poncelet, Denis
Cell-encapsulation is used for preventing therapeutic cells from being rejected by the host. The technology to encapsulate cells in immunoprotective biomaterials, such as alginate, commonly involves application of an electrostatic droplet generator for reproducible manufacturing droplets of similar size and with similar surface properties. As many factors influencing droplet formation are still unknown, we investigated the impact of several parameters and fitted them to equations to make procedures more reproducible and allow optimal control of capsule size and properties. We demonstrate that droplet size is dependent on an interplay between the critical electric potential (Uc, ), the needle size, and the distance between the needle and the gelation bath, and that it can be predicted with the equations proposed. The droplet formation was meticulously studied and followed by a high-speed camera. The X-ray photoelectron analysis demonstrated optimal gelation and substitution of sodium with calcium on alginate surfaces while the atomic force microscopy analysis demonstrated a low but considerable variation in surface roughness and low surface stiffness. Our study shows the importance of documenting critical parameters to guarantee reproducible manufacturing of beads with constant and adequate size and preventing batch-to-batch variations.